KOMPARASI HASIL BELAJAR EKONOMI DENGAN PEMBELAJARAN KOOPERATIF TIPE JIGSAW DAN STAD - Ferdesi Hanafia; R. Gunawan Sudarmanto; Darsono Darsono (Jurnal Studi Sosial / Journal of Social Studies, 2013)
This study was conducted to determine the difference between the results of the economic study learning with Jigsaw and STAD models. The results showed: (1) there is a difference between the results of the economic study with the learning process STAD and the learning model Jigsaw that is seen from the beginning skill level such as high, medium, low, (2) there is difference in learning outcomes between students who are given the economics of learning with Jigsaw and STAD models, (3) there are differences in learning outcomes between students who are capable of economics initial high, medium and low, (4) there is no interaction between Jigsaw and STAD learning models with high initial ability, medium and low to the results of the economic study, and (5) there is difference in effectiveness between the model STAD and Jigsaw which is learning with Jigsaw model more effective. This research used experiment research method with factorial design approach.Penelitian ini dilakukan untuk mengetahui perbedaan hasil belajar ekonomi antara model pembelajaran Jigsaw dan model STAD. Hasil penelitian menunjukan: (1) ada perbedaan hasil belajar ekonomi antara proses pembelajaran dengan model pembelajaran Jigsaw dan STAD yang dilihat dari tingkat kemampuan awal tinggi, sedang, rendah; (2) ada perbedaan hasil belajar ekonomi antara siswa yang diberi pembelajaran dengan model Jigsaw dan STAD; (3) ada perbedaan hasil belajar ekonomi antara siswa yang berkemampuan awal tinggi, sedang dan rendah; (4) tidak ada interaksi antara model pembelajaran Jigsaw dan STAD dengan kemampuan awal tinggi, sedang dan rendah terhadap hasil belajar ekonomi; dan (5) ada perbedaan efektifitas antara model Jigsaw dan STAD di mana model pembelajaran Jigsaw lebih efektif. Penelitian ini menggunakan metode penelitian eksperimen dengan pendekatan desain faktorial.Kata kunci: hasil belajar, kemampuan awal, model pembelajaran